Respuesta :

Answer:

   41. (2) x² - 3x - 4 =0

Step-by-step explanation:

Question 41

Standard form of polynomial

  • x² - (sum of roots) + product of roots = 0
  • (2) x² - 3x - 4 =0

Answer:

(2)  [tex]x^2-3x-4=0[/tex]

Step-by-step explanation:

Standard form of a quadratic equation:  [tex]ax^2+bx+c=0[/tex]

When factoring a quadratic (finding the roots) we find two numbers that multiply to [tex]ac[/tex] and sum to [tex]b[/tex], then rewrite [tex]b[/tex] as the sum of these two numbers.

So if the roots sum to 3 and multiply to -4, then the two numbers would be 4 and -1.

[tex]\implies b=1+-4=-3[/tex]

[tex]\implies ac=1 \cdot -4[/tex]

As there the leading coefficient is 1, [tex]c=-4[/tex].  

Therefore, the equation would be:  [tex]x^2-3x-4=0[/tex]

Proof

Factor  [tex]x^2-3x-4=0[/tex]

Find two numbers that multiply to [tex]ac[/tex] and sum to [tex]b[/tex].

The two numbers that multiply to -4 and sum to -3 are:  -4 and 1.

Rewrite [tex]b[/tex] as the sum of these two numbers:

[tex]\implies x^2-4x+x-4=0[/tex]

Factorize the first two terms and the last two terms separately:

[tex]\implies x(x-4)+1(x-4)=0[/tex]

Factor out the common term  [tex](x-4)[/tex]:

[tex]\implies (x+1)(x-4)=0[/tex]

Therefore, the roots are:  

[tex](x+1)=0 \implies x=-1[/tex]

[tex](x-4)=0 \implies x=4[/tex]

So the sum of the roots is:  -1 + 4 = 3

And the product of the roots is:  -1 × 4 = -4

Thereby proving that  [tex]x^2-3x-4=0[/tex]  has roots whose sum is 3 and whose product is -4.